Competing pathways in the near-UV photochemistry of acetaldehyde. Issue 22 (24th May 2017) - Toulson, Benjamin W.; Kapnas, Kara M.; Fishman, Dmitry A.; Murray, Craig
Abstract : Time-resolved ion imaging measurements have been performed to explore the photochemistry of acetaldehyde at photolysis wavelengths spanning the range 265–328 nm. Abstract : Time-resolved ion imaging measurements have been performed to explore the photochemistry of acetaldehyde at photolysis wavelengths spanning the range 265–328 nm. Ion images recorded probing CH3 radicals with single-photon VUV ionization show different dissociation dynamics in three distinct wavelength regions. At the longest photolysis wavelengths, λ > 318 nm, CH3 radicals are formed over tens of nanoseconds with a speed distribution that is consistent with statistical unimolecular dissociation on the S0 surface following internal conversion. In the range 292 nm ≤ λ ≤ 318 nm, dissociation occurs almost exclusively on the T1 surface following intersystem crossing and passage over a barrier, leading to the available energy being partitioned primarily into photofragment recoil. The CH3 speed distributions become bimodal at λ < 292 nm. In addition to the translationally fast T1 products, a new translationally slow, but non-statistical, component appears and grows in importance as the photolysis wavelength is decreased. Photofragment excitation (PHOFEX) spectra of CH3 CHO obtained probing CH3 and HCO products are identical across the absorption band, indicating that three-body fragmentation is not responsible for the non-statistical slow component. Rather, translationally slow products are attributed to dissociation on S0, accessed via a conical intersection between the S1 and S0 surfaces at extended C–C distances. Time-resolved ion images of CH3 radicals measured using a picosecond laser operating at a photolysis wavelength of 266 nm show that product formation on T1 and S0 via the conical intersection occurs with time constants of 240 ps and 560 ps, respectively.